Research on Dewatering Ability of Municipal Sludge under the Treatment of Coupled Acid and Microwave - Xudong Zhang; Peng Ye; Yajun Wu; Zhen Guo; Yuan Huang; Xingtao Zhang; Yuncong Sun; Haiqiang Zhang (Geofluids)
Municipal sludge is a by-product of urban sewage treatment; it has high water content and contains many hydrophilic extracellular polymeric substances (EPS). It is difficult to achieve deep dewatering of sludge. Therefore, it is necessary to find an efficient method to treat sludge. In this study, an acid-microwave treatment method was proposed to improve the dewatering ability of sludge. A vacuum filtration test and particle size analysis test were used to explore the improvement effect of dehydration performance. After centrifugation, the concentrations of soluble proteins and polysaccharides in the supernatant were measured to explore the disintegration of acid-microwave treatment on EPS. Finally, the microstructure of sludge treated by acid-microwave was studied via the SEM test. The results showed that short-term microwave radiation was conducive to sludge dewatering. However, the sludge dewatering performance deteriorated significantly when the treatment time was too long. The optimal microwave treatment condition was 700 W for 180 s, and the SRF of sludge was the lowest, which was 10.11×1012 m/kg. After acid-microwave treatment, sludge particle size increased significantly. The concentration of protein and polysaccharide in supernatant increased with the increase of microwave treatment time. Acid-microwave treatment could significantly improve the release efficiency of the polysaccharide. Through the SEM test, it can be verified that the bulk floc structure of sludge is broken after microwave treatment, and acid-microwave treatment is beneficial to the aggregation of floc fragments to form large particles, which can provide larger pores for drainage.